Control strategy for the core power in an accelerator drive sub-critical system - Xinxin Li; Yuan He; Wenjing Ma; Wenjuan Cui; Zhiyong He; Detai Zhou; Hai Zheng; Feng Yang; Yuhui Guo; Haihua Niu; Kai Yin; Shiwu Dang (Nuclear Engineering and Technology)
This paper reports the control strategy for the core power in an accelerator drive sub-critical (ADS) system. In an ADS system, the intense external neutron source provided by a proton accelerator coupled to a spallation target is used to drive a sub-critical reactor. The proposed control strategy is to control the reactor power by adjusting the proton beam power, where the beam power is adjusted by changing either the duty factor or the intensity of the proton beam. As an example, the reactor power control of the China initiative Accelerator Driven System (CiADS) facility has been studied by adjusting the beam power. Firstly, the beam power is set roughly by assigning a new duty factor, where the duty factor is set by changing the beam macro-pulse length and the pulse repetition rate of the proton beam. Both the pulse length and the repetition rate are assigned by a timing system. Secondly, the power is adjusted precisely by changing the beam intensity. To change continuously the beam intensity, an adjustable aperture is used to block the outer particles of the beam line in the accelerator. In order to evaluate the proposed control strategy, a CiADS core model is built based on the multi-node point reactor dynamics model. Three cases, the start of the facility, the decrease of core power and the increase of core power, have been simulated with the model. The simulation results indicate that the control strategy for the core power by changing either the duty factor or the intensity of the proton beam works very well during the operation of the facility.